Inovasi Terraplanter Baby Tears Sebagai Bisnis Kekinian Paket Hadiah (Hampers) Florikultura Indoor - Safitri, Zahra Syafira; Kaniyasari, Amartya Esa; Kamila, Baiq Nazla Safa; Nadiah, Firda; Hidayat, Syahril Afif; Damayanti, Ratnaningsih (Universitas Bunda Mulia, 2023)
Reduction of green land in urban areas from 2017 which was before 7.75 million hectares to be only 7.1 million hectares in 2018. This condition is a problem for people who want to grow ornamental plants. During the pandemic, the trend of ornamental plants is on the rise in the market. Therefore, the presence of an innovative Plant.et product in the form of plant hampers consisting of terraplanter baby tears that apply hydraulic planting technology by growing outside the terraplanter tube without using soil planting media and QR code system. The purpose of this innovation is to be a solution to the problem of reducing green land, developing unique and superior businesses based on post-pandemic technology.The method of implementation on Plant.et product is carried out by determining product design, product quality testing, determining product uniqueness and excellence, market surveys, and marketing strategies. The results showed that Plant.et products are in great demand among teenagers with a female gender and has been sale more 100 pcs. The advantages and uniqueness of Plant.et product in the form of a hydraulic plant outside the terraplanter tube with a QR code system packed with hampers. Therefore, Plant.et product has great potential to be developed.